Ageing in the era of precariousness. Care and intergeneration relations among Portuguese families in times of austerity - Lima, Antónia (Internacional Conference: Caring for elderly and dependent people: Promoting gender equality and social justice, 2019)
Focusing simultaneously on aging, interpersonal relationships, care, and economic interests and how they intersect with each other I will argue that the role of family relations and personal networks are central dimensions to understand the different dimensions of ageing and of taking care of one’s elderly in the era of precariousness. Countries from southern Europe experienced the impact of severe austerity policies between 2011-2015. Although analysis of this conjuncture are usually centered on its economic and political character, its consequences are evident in every dimension of social life. Departing from a discussion on the recent transformations in ageing in Portugal, this paper will examine 1) how people integrate informal systems of care to take care of their elderly while living in outmost precarious lives; 2) how intergeneration relations changed as consequence of the transformations of the labour market and the increasing of unemployment or precarious ways to make a living; 3) how the financial resources of the elderly are an important economic dimension to the family; 4) how this conjuncture is changing both interpersonal relations among family members and the power/dependence relations among family members and it is altering the family patterns of residence. Through an ethnographic research among Portuguese families between 2012 and 2015, in the paper I will argue that elders have gained a renewed role in families, and that their former dependent situation are now frequently turned into central power positions due to the importance of their retirement pensions. The transformation of family relations in this conjuncture only tackle the immediate effects of austerity times but also reveal new social and economic meanings of care, support and solidarity practices. Care – austerity – Portugal – intergerational relations – interpersonal relations